Red Clam Shell based Basic Heterogenous Catalyst for Transesterification of Ricinus communis L Oil Synthesis and Characterization - Ibrahim I; Syam AM; Meriatna M; Mulyawan R; Munira S; Aulia MR; Munouwarah L (LPPM Universitas Malikussaleh, 2022)
The transesterification process in synthesizing biodiesel utilizes basic catlalyst to enhance the reaction. This research investigated the use of red clam shell based basic heterogenous catalyst for biodiesel production from Ricinus communis L oil. The purpo21se of this research was to optimize the heterogenoeus catalyst synthesis and comprehend the synthesized catalyst characterization. Red clam shell powder was prepared through 750°C, 800°C and 850°C calcination temperatures for 4 hours. The synthesized heterogeneous catalysts were characterized through SEM, XRD and FTIR in order to comprehend the morphology, its content and the present functional groups existed. It was founs out that the red clam shell ash had porous structure with its regularity increases with increasing calcinating temperature. Besides, according to XRD analysis the porous material with the highest amount of CaO presented was determined to be at 800°C calcination temprature to be 92.6% alongwith CaCO3 indicating the basic properties. Moreover, the functional groups presented on heterogeneous catalyst were observed to be CaO as the sharpest peak was at 3653.82 cm-1 and CaCO3 at 1452.40 cm-1, 1004.91 cm-1 and broad peak around 500 cm-1 with 800°C calcination temperature. Two percent of 800°C calcinated catalyst was utilized for transesterification with 1:8 oil to methanol ratio at 60°C reaction temperature. It was figured out that the synthesized biodiesel exhibited 4.587 x 10-3 Pas and 0.878 kgm-3 as its viscosity and density respectively. The use of red clam shell based catakyst for Ricinus communis L oil transesterification for biodiesel production was proven to be potential and demands further study on its application for transesterification reaction.